Autosomal dominant mesomandibular fibro-osseous dysplasia: a self-resolving inherited fibro-osseous lesion of the jaws - Koutlas, Ioannis; Forsman, Cynthia; Kyrkanides, Stephanos; Oetting, William; Petryk, Anna (Frontiers in Physiology, 2012)
A hereditary congenital condition characterized by a fibro-osseous lesion sharing some features with fibrous dysplasia and affecting the middle aspect of the mandible is presented. The condition was initially described as congenital monostotic fibrous dysplasia in two siblings, a male and a female. However, there is sufficient evidence that the disorder is autosomal dominant since it has been encountered in two of four children, both males, of the female propositus and one child, a boy, of the male propositus. All patients presented at birth or right after birth with enlargement of the middle part of the mandible. Radiographs from affected individuals have shown mesomandibular enlargement with irregular trabeculation akin of “ground-glass” appearance. Histologically, samples from all patients revealed woven bone proliferation in a cellular fibroblastic stroma. Interestingly, the originally described siblings, now in their 30s, have no evidence of jaw lesions either radiographically or clinically, thus indicating that the condition is self-limiting or self-resolving. An autosomal dominant mode of inheritance with apparent male predilection is favored. The molecular basis of this condition is currently unknown. However, the location of the lesions in the middle aspect of the mandible suggests dysregulation of Bone Morphogenetic Protein (BMP) signaling since BMPs regulate mandibular morphogenesis in utero, particularly in the medial region as well as postnatal bone remodeling. Immunohistochemical evaluation for a BMP-binding protein Twisted Gastrulation (TWSG1) revealed mosaic pattern of staining, with some cells, including osteoclasts, strongly stained and others exhibiting faint or no staining, thus supporting active regulation of BMP signaling within the lesion. Future investigations will determine if dysregulation of BMP signaling plays a causative role or rather reflects secondary activation of repair mechanisms and/or bone remodeling.